2022
DOI: 10.3390/ijms231911985
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Recurrence of Gastric Cancer Using the Textural Features of Perigastric Adipose Tissue on [18F]FDG PET/CT

Abstract: This study aimed to assess the relationship between the histopathological and textural features of perigastric adipose tissue (AT) on 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT) and to evaluate the prognostic significance of perigastric AT textural features in predicting recurrence-free survival (RFS) in patients with gastric cancer. Sixty-nine patients with gastric cancer who underwent staging [18F]FDG PET/CT and subsequent curative surgery were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…Numerous studies have demonstrated that a positive prognosis for gastric cancer is related to high expression of TILs (CD4, CD8) [35,48]We find that the derived parameters of gray level co-occurrence matrix (GLCM) play an important role. GLCM played an important role in predicting CD8 + TIL density, which is consistent with previous reports that radiomics metrics of GLCM were dominant in models predicting CD8 + TIL density in renal clear cells [49]. This study also found a close relationship between the radiomics parameters of GLCM and CD4 + TILs.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have demonstrated that a positive prognosis for gastric cancer is related to high expression of TILs (CD4, CD8) [35,48]We find that the derived parameters of gray level co-occurrence matrix (GLCM) play an important role. GLCM played an important role in predicting CD8 + TIL density, which is consistent with previous reports that radiomics metrics of GLCM were dominant in models predicting CD8 + TIL density in renal clear cells [49]. This study also found a close relationship between the radiomics parameters of GLCM and CD4 + TILs.…”
Section: Discussionsupporting
confidence: 91%
“…This inflammatory process in adipose tissue has been shown to be significantly correlated with CT attenuation and the FDG uptake of adipose tissue in previous studies [15,16,22]. A non-human primate biopsy study demonstrated that increased VAT HU was related to increased extracellular matrix fibrosis and a decreased size of adipocytes in VAT, which is consistent with the findings of inflamed adipose tissue near the cancerinvasive front [22].…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, two imaging parameters, mean computed tomography (CT) attenuation on unenhanced CT images and mean 2-deoxy-2-[ 18 F]fluoro-D-glucose (FDG) uptake on positron emission tomography (PET) images, have been proposed to estimate qualitative changes in adipose tissue in imaging studies [12][13][14]. In previous studies, these two imaging parameters measured from SAT and VAT were shown to be correlated with the degree of inflammatory changes in adipose tissue, as well as significantly associated with survival in patients with diverse malignant diseases, including gastric cancer, hepatocellular carcinoma, and colorectal cancer [12,[14][15][16][17]. Considering the significant relationship that has been shown to exist between adiposity and the prognosis of cholangiocarcinoma, imaging parameters customized for the qualitative features of adipose tissue could also have significant clinical value for predicting the prognosis of cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The four SUV intensity histogram parameters, kurtosis, skewness, entropy, and uniformity, represent the shape, asymmetry, randomness, and homogeneity of the SUV distribution in the SUV intensity histogram [ 20 ]. A lesion that shows high entropy and low uniformity in the histogram is considered to have increased metabolic heterogeneity [ 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%